2017
DOI: 10.4103/0972-9941.186687
|View full text |Cite
|
Sign up to set email alerts
|

Impact of seniority on operative time and short-term outcome in laparoscopic cholecystectomy: Experience of an academic Surgical Department in a developing country

Abstract: INTRODUCTION:Resident participation in laparoscopic cholecystectomy (LC) is one of the first steps of laparoscopic training. The impact of this training is not well-defined, especially in developing countries. However, this training is of critical importance to monitor surgical teaching programmes.OBJECTIVE:The aim of this study was to determine the impact of seniority on operative time and short-term outcome of LC.DESIGNS AND SETTINGS:We performed a retrospective study of all consecutive laparoscopic cholecys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 17 publications
2
7
0
2
Order By: Relevance
“…In our study, factors found to be independently predictive of operative duration were patient age, gender, ASA grade, operative indication, BMI, CBD diameter, gallbladder wall thickness, pre-operative CT scan, planned intra-operative cholangiogram and the number of previous surgical admissions. These factors are broadly similar to previous work by other researchers [ 12 , 20 , 21 ]. Our study expands on their work and has developed a clinically useful scoring tool.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In our study, factors found to be independently predictive of operative duration were patient age, gender, ASA grade, operative indication, BMI, CBD diameter, gallbladder wall thickness, pre-operative CT scan, planned intra-operative cholangiogram and the number of previous surgical admissions. These factors are broadly similar to previous work by other researchers [ 12 , 20 , 21 ]. Our study expands on their work and has developed a clinically useful scoring tool.…”
Section: Discussionsupporting
confidence: 89%
“…These factors are broadly similar to previous work by other researchers [12, 20, 21]. Our study expands on their work and has developed a clinically useful scoring tool.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Hence, we recommend that procedures longer than 90 minutes should not be a contraindication for same-day discharge. Previous studies have reported longer operating durations when trainees were involved [ 27 ]. However, the longer operating times in our cohort were not related to inexperience of the surgeon, as only two of the 38 prolonged operations were operated by trainee surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…Зростання тривалості операцій у групі симультанних лапароскопічних операційних втручань, виконаних власною розробленою технікою, склав час, який не може конкурувати із тривалістю окремої повноцінної операції, якби їх виконували незалежно у різні періоди часу. Наприклад тривалість лапароскопічної холецистектомії у різних дослідників складає більше за отриману різницю, так само як і час, необхідний для виконання лапароскопічної холецистектомії у цьому дослідженні [16,17]. Також дослідники з інших публікацій вказують на часто переважаючий час, необхідний для створення доступу та зашивання ран, а також, при наявності злукового процесу під час повторної операції, для створення операційної зони [18].…”
Section: обговоренняunclassified